Security Management Information Systems Through Fire Wall Concepts, Logics And Problem Of Deleted Data: An Empirical Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of the study is to learn more about the opinions regarding Security Management Information Systems by examining Fire Wall principles, Logics and findings, and the issue with erased data. In order to learn more about respondents’ opinions regarding Security Management Information Systems, a quantitative research methodology was applied. A Likert scale was used in the creation of the questionnaire. The theoretical study's conclusions served as the foundation for the queries. Still, 423 systems practitioners took the time to complete the survey. The data gathered from the surveys has been examined using the statistical application SPSS 20. The coefficient summary shows that the factor's beta values are 0.066, 0.359, and 0.536, which are generally indicative of the impact on Security Management Information System (SMIS). Additionally, the factor's beta values are 0.750 for ISA to FWS, 0.910 for LBS, and 0.873 for ISA to PDDR, which accurately represent the influence of Information Security Awareness (ISA) on Firewall security, Logic Based Security, and Problem of Deleted Data Recovery. The analysis found that there were flaws in the information security practices' conception, execution, and upkeep. It is essential for management to conduct an assessment of their information security procedures since they serve as a safeguard for the organization's and information-related assets.